Լեվոն Մեծագործի և Հովհաննես Զ Սսեցու հարաբերությունների պատմությունից (1203-1219 թթ.) - Հովհաննիսյան, Արամ
Работа посвящена исследованию истории взаимоотношений основателя Киликийской Армении короля Левона Великого и Ованнеса Ссеци. В начале рассматриваются обстоятельства, при которых Ованнес был избран католикисом. Далее касаемся Церковного Собора Сиса и решению, которое было принято католикосом относительно Захарии амирспасалара. В завершении работы представлен конфликт, возникший между армянским королем и католикосом Ованнесом, разделение католикосского престола и их примирение. The article deals with the history of the relationships between King Levon Metsagorts and Hovhannes Ssetsi. Firstly we have revealed and have given the circumstances under which Hovhannes Bishop was elected as Catholikos. Then we have mentioned both the Church council held in Sis and the decision that was given to Zaqareh Amirspasalar/commander by the Catholikos himself. The article ends in statements on the controversy that aroused between King Levon and Catholikos Hovhannes, as well as the reconciliation between them.
Keywords: Հայոց պատմություն